Novice teachers’ motivations and beliefs to develop pronunciation in the english language - Linhares, Marcilon de Sousa (2023)
This research aims to understand the motivations and beliefs of novice English teachers regarding their pronunciation and to analyze how they shape and develop their self-motivational systems and beliefs concerning English pronunciation. To achieve this goal, interviews were conducted with three teachers, encompassing their experiences in public schools, private institutions, and independent language courses. The interview questions covered relevant topics, including pronunciation, English language teaching, English variants, as well as motivations and feelings related to the study and development of the subject. In order to deepen the understanding of motivations, the L2 Motivational Self-System, proposed by Zoltan Dörnyei, was employed, which encompasses the self-images that language learners create regarding who they need to be, who they wish to become, and who they fear becoming. The data collected during the interviews proved satisfactory for resolving the research questions, providing insights into participants' beliefs, emotions, motivations, and considerations on topics such as accent, intelligibility, English variants, and teachers' aspirations. However, these aspects brought a different approach to the conclusion of the hypotheses in this study.